2018
DOI: 10.1016/j.bbr.2017.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Memantine improves outcomes after repetitive traumatic brain injury

Abstract: Repetitive mild traumatic brain injury (rmTBI; e.g., sports concussions) is common and results in significant cognitive impairment. Targeted therapies for rmTBI are lacking, though evidence from other injury models indicates that targeting N-methyl-d-aspartate (NMDA) receptor (NMDAR)-mediated glutamatergic toxicity might mitigate rmTBI-induced neurologic deficits. However, there is a paucity of preclinical or clinical data regarding NMDAR antagonist efficacy in the rmTBI setting. To test whether NMDAR antagoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…Factors that influenced p‐tau development in the assessed studies were the total number of impacts and length of time between impacts. Where a greater number of impacts were administered, p‐tau was demonstrated in the acute phase (Mei et al, ), and at times also remained at high levels even at delayed follow‐up (Briggs et al, ; Kane et al, ). Following single impacts, p‐tau expression was less likely to be seen (Namjoshi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Factors that influenced p‐tau development in the assessed studies were the total number of impacts and length of time between impacts. Where a greater number of impacts were administered, p‐tau was demonstrated in the acute phase (Mei et al, ), and at times also remained at high levels even at delayed follow‐up (Briggs et al, ; Kane et al, ). Following single impacts, p‐tau expression was less likely to be seen (Namjoshi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, tau transgenic mice (uninjured) treated with epothilone D showed attenuated tau pathology and improved cognition compared to wild type mice (Brunden et al, 2010;Zhang et al, 2012a). Interestingly, memantine administered after rmTBI in adult C57Bl6 mice reduced markers of tau phosphorylated at Thr231 (Mei et al, 2018). Other studies report p-tau-reducing effects of antioxidants (Du et al, 2016), PP2A activation (Shultz et al, 2015;Tan et al, 2016), DHA treatment (Begum et al, 2014), endocannabinoids (Zhang et al, 2015), and JNK inhibition (Tran et al, 2012).…”
Section: Therapies Targeting Tau In Tbimentioning
confidence: 99%
“…This mechanism of NMDA-mediated damage has been shown to occur in several CNS injury models, including TBI and stroke ( 81 ). In animal models of TBI, memantine treatment decreased the accumulation of phosphorylated tau proteins in the cortical tissue at early, although not chronic time points (up to 30 days post-injury), and suppressed microglial activation ( 82 ). A similar study showed that memantine decreased cerebral infarct area, increased neuronal survival in the perilesional hemisphere, and decreased levels of microgliosis and astrogliosis ( 83 ).…”
Section: Traumatic Brain Injurymentioning
confidence: 99%